Factors Influencing Medication Adherence Among Individuals with Mental Disorders in The Service Area of The Medan Denai Community Health Center - Mira Dwi Handayani; Henny Syafitri; Donal Nababan (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2025)
This study aims to analyze the factors influencing medication adherence in patients with mental disorders in the Medan Denai Community Health Center (Puskesmas Medan Denai). This study employed a quantitative analytical survey design. The study sample consisted of 100 respondents selected using a simple random sampling technique. Data were collected through a questionnaire measuring variables such as family support, psychoeducation, economic status, and support from healthcare professionals, as well as medication adherence. Statistical tests used to analyze the data were the chi-square test and logistic regression. These findings indicated that family support, psychoeducation, economic status, and assistance from healthcare professionals significantly impacted medication adherence (p<0.05), with economic status being the most influential factor, followed by support from healthcare professionals and family support. The implications of these findings highlight the importance of family and healthcare professional support in improving medication adherence. Additionally, increasing access to psychoeducational services is essential for enhancing adherence among patients with mental disorders at the Medan Denai Community Health Center.